A phase I study of cabazitaxel in combination with platinum and 5-fluorouracil (PF) in locally advanced squamous cell carcinoma of head and neck (LA-SCCHN). (August 2017) - Camille, Nadia; Rozehnal, John; Roy, Elizabeth; Uczkowski, Dariusz; Olson, Ashely; Genden, Eric; Teng, Marita; Bakst, Richard; Gupta, Vishal; Posner, Marshall; Misiukiewicz, Krzysztof
Abstract: Background: There is a clinical need to improve outcomes for patients with locally advanced squamous cell carcinoma of the head and neck (LA-SCCHN), especially in Human Papilloma Virus (HPV) negative and HPV positive subtypes with a significant history of tobacco use. In animal models bearing SCCHN, Cabazitaxel showed an excellent response rate compared to docetaxel and might prove useful in treatment of patients. The primary objective of this study was to determine the dose-limiting toxicity (DLT) and maximum tolerated dose (MTD) of cabazitaxel when combined with cisplatin and 5-fluorouracil (PF) in induction chemotherapy (IC) for patients with SCCHN. Cabazitaxel-PF IC administered in 3 cycles (each 21 days) followed by concurrent chemoradiation (CRT) or surgery has been evaluated to assess overall response rate (ORR) and progression-free survival (PFS) in this population. Methods: This phase I study employed a standard 3 + 3 design. DLT was defined as grade 4 or 5 toxicity or grade 3 toxicity lasting >7 days. Out of 40 consented patients with stage IV, curable, previously untreated, LA-SCHHN and poor prognosis, 35 (32M, 3F) were enrolled and evaluated for toxicity: 19 oropharynx, 10 larynx, 2 oral cancer, 1 nasopharynx and 3 hypopharynx. Five dose levels of cabazitaxel (10, 12.5, 15, 17.5 and 20 mg/m 2 ) were tested in combination with cisplatin 100 mg/m 2 and 5-fluorouracil (5-FU) 800 mg/m 2 /d × 4 days. Dose escalation for cabazitaxel was terminated upon the occurrences of 2 DLTs and the establishment of MTD. Cabazitaxel was then further escalated with cisplatin 75 mg/m 2 and 5-FU 800 mg/m 2 /d × 4 days in the subsequent 3 dose levels (17.5, 20 and 22.5 mg/m 2 ). In the expansion cohort, 9 patients were enrolled at the 22.5 mg/m 2 dose level. Following 3 cycles of IC, patients were evaluated for clinical, radiographic, and pathologic response to cabazitaxel-PF before beginning CRT or surgery. Results: There were two DLTs (grade 4 hyperuricemia; neutropenic fever, sepsis, and grade 4 thrombocytopenia) among 2 patients in cohort 5 at the dose of 20 mg/m 2 of cabazitaxel. There were no DLTs reported with cohorts using a lower dose of cisplatin, even in the expansion cohort. The study was stopped at the dose of 22.5 mg/m 2 in accordance with the initial study design. With 33 evaluable patients for response, the Overall Response Rate (ORR) rate was 57.6%: 9.1% Complete Responses (CR) and 48.5% Partial Responses (PR) were noted. Conclusions: The recommended phase II dose for cabazitaxel in combination with cisplatin 75 mg/m 2 and 5-FU 800 mg/m 2 /d × 4 days is 22.5 mg/m 2 and for cisplatin 100 mg/m 2 and 5-FU 800 mg/m 2 /d × 4 days is 17.5 mg/m 2 . With a median follow-up of 39 months, PFS for the entire non-metastatic population at 3 years was approximately 58%.